2020
DOI: 10.15541/jim20200083
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Hyperstoichiometric UO2Crystals

Abstract: Uranium dioxide is a potential multi-functional material as well as nuclear rod. It exhibits excellent semiconductor performance and anti-irradiation ability. It has the similar band gap (1.3 eV) of silicon crystal (1.1 eV), its Seebeck coefficient is 4 times of the commercial thermoelectric material BiTe, and it shows higher conversion efficiency of solar cells due to its nearly full absorption. These properties make it great potential applications in the fields of semiconductor, solar energy and thermoelectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Lira et al reported the photoluminescence of the Er: BSO crystal [18]. Previously, we have reported rare-earth ions and Ge 4+ -and U 4+ -doped BSO laser crystals, and laser output was realized in Ho 3+ : BSO and Tm 3+ : BSO crystals [19][20][21][22]. In the present work, the growth and spectral properties of the Er/Yb: BSO crystal are reported.…”
Section: Introductionmentioning
confidence: 56%
“…Lira et al reported the photoluminescence of the Er: BSO crystal [18]. Previously, we have reported rare-earth ions and Ge 4+ -and U 4+ -doped BSO laser crystals, and laser output was realized in Ho 3+ : BSO and Tm 3+ : BSO crystals [19][20][21][22]. In the present work, the growth and spectral properties of the Er/Yb: BSO crystal are reported.…”
Section: Introductionmentioning
confidence: 56%